Corticosteroid Utilization before and after Initiation of Biologic Dmards between Patients with Rheumatoid Arthritis - Yagiz, Burcu; Coskun, Belkis Nihan; Kiraz, Sedat; Ertenli, Ihsan; Kucuksahin, Orhan; Dalkilic, Ediz; Kalyoncu, Umut (Wiley, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-for-Rheumatology-Health-Professionals (ARHP) -- OCT 19-24, 2018 -- Chicago, IL